Healthy housing - A Residential Project for Students - Blomstrand, Sara (My University, 2020)
Social isolation is a well-known health problem among our elderly population. An American study (Holt-Lunstad, J., B. Smith, T., Layton, J.B., 2010) stated that the lack of social relationships has comparable negative effects on the health as smoking. However, social isolation is not only a health issue in the ageing population, due to a report made by the Swedish Board of Student Finance (CSN, 2018) 20% of students state that they always or often experience loneliness and 15% state that they avoid social situations. I find the severe health concerns connected to social isolation to be an under discussed topic and therefore I want to explore what can be done in our built environment to prevent health issues linked to social isolation. As our homes are the place where we spend most of our time, I find it to be the most fitted environment to work with social isolation. Housing shortage in urban areas is a major problem, not at least for students. Therefore, I want to explore how we can build health promoting housing solutions in an urban context for students. This thesis will investigate how we can use architecture to build homes that makes us experience well-being by creating stress reducing environments and create possibilities for social meetings. This thesis will investigate the following questions: How can one create housing solutions to benefit well-being and reduce social isolation? I want to investigate this by studying literature, studying references projects, include the users by making a survey for students and use the design process to analyse and test my findings through design. This project will result in a student housing project. The building both need to serve the basic functions needed in a home but also to add extra qualities for the inhabitants giving them space and possibilities for social interactions. The goal is to provide housing in an urban area that are health promoting and promote social interactions.